Impact of ultraviolet light on quality attributes of stored fresh-cut mango - Lucía ROMERO (Annals of the University Dunarea de Jos of Galati. Fascicle VI: Food Technology, 2017)
Mango (Mangifera indica L.) is one of the most important tropical fruits worldwide being considered a good source of antioxidants, carotenoids and ascorbic acid. For this reason, the effects of UV light treatments on bacterial contaminants and quality parameters of fresh-cut mango were investigated. The mangoes were selected, washed, disinfected, cut, inoculated with Escherichia coli and Listeria innocua at a level of 109 and 107 CFU/g, respectively and packaged. The artificially contaminated and non-contaminated mango pieces were treated with UV light using different doses of 2.064 and 1.479 kJ/m2 , respectively, at two distances (8 and 15 cm) and further stored at 4˚C for 15 days. The results showed that high doses of UV light and low distance between lamp and sample generate higher levels of bacterial reduction. L. innocua showed lower sensitivity to UV treatment than E. coli. The physicochemical analyses (colour, texture and pH) were performed every 3 days on the non-contaminated mango samples. The UV treatments had a beneficial effect on stored mangoes texture, while the color deteriorated over time. pH was not affected by the ultraviolet light treatments.